TRACE ELEMENT AND PLATINUM GROUP ELEMENT DISTRIBUTIONS AND THE GENESIS OF THE MERENSKY REEF, WESTERN BUSHVELD COMPLEX, SOUTH AFRICA - Wilson A.; Chunnett G. (My University, 2006)
The Merensky Reef of the Bushveld Complex is one of the worlds largest resources of platinum group elements (PGE); however, mechanisms for its formation remain poorly understood, and many contradictory theories have been proposed. We present precise compositional data [major elements, trace elements, and platinum group elements (PGE)] for 370 samples from four borehole core sections of the Merensky Reef in one area of the western Bushveld Complex. Trace element patterns (incompatible elements and rare earth elements) exhibit systematic variations, including small-scale cyclic changes indicative of the presence of cumulus crystals and intercumulus liquid derived from different magmas. Ratios of highly incompatible elements for the different sections are intermediate to those of the proposed parental magmas (Critical Zone and Main Zone types) that gave rise to the Bushveld Complex. Mingling, but not complete mixing of different magmas is suggested to have occurred during the formation of the Merensky Reef. The trace element patterns are indicative of transient associations between distinct magma layers. The porosity of the cumulates is shown to affect significantly the distribution of sulphides and PGE. A genetic link is made between the thickness of the Merensky pyroxenite, the total PGE and sulphide content, petrological and textural features, and the trace element signatures in the sections studied. The rare earth elements reveal the important role of plagioclase in the formation of the Merensky pyroxenite, and the distribution of sulphide.
Keywords: Merensky Reef; platinum group elements; trace elements